Workshop on Improving Teacher Skills in Designing Project-Based Mathematics Learning to Develop Students' Critical Thinking Skills - Sofyan, Deddy; Rosada, Cucu; Rosadi, Dadang; Gandara, Endang; Aryani, Rindu; Yulianti, Yanti; Koswara, Undang; Supiantini, Eulis; Sugandi, Sugandi; Ramdona, Eri Muhammad; Cahyati, Lilis Sri; Ramli, Lili Jaenudin (Fakultas Kewirausahaan Universitas Garut, 2023)
This community service aimed to enhance mathematics teachers' skills in designing Project-Based Learning (PjBL)to foster students' critical thinking. The workshop, held on October 14, 2023, at SMAN 11 Garut, targeted high school (SMA/SMK) mathematics teachers. Activities included theoretical presentations, hands-on project design, and assessment development. Results showed a significant positive impact on teachers' understanding of PjBL and its link to critical thinking (evidenced by increased pre-test/post-test scores). Teachers also demonstrated improved practical skills in designing relevant math projects and authentic assessments, alongside a heightened awareness of critical thinking's importance. While recognizing potentials and challenges in PjBL implementation, the workshop boosted teacher confidence and motivation. This is a crucial step toward more meaningful math education and developing future-ready critical thinkers, with continued mentoring recommended for sustained impact.